Gender differences in the electrocardiogram screening of athletes - Bessem, B. B.; de Bruijn, M. M. C.; Nieuwland, W. W. (Journal of Science and Medicine in Sport, 2017)
Objectives: Gender-related differences are frequently used in medicine. Electrocardiograms are also subject to such differences. This study evaluated gender differences in ECG parameters of young athletes, discussing the possible implications of these differences for ECG criteria used in the cardiovascular screening of young athletes. Design: Observational cross-sectional study. Methods: In 2013 and 2014 all the ECGs from the cardiovascular screenings performed at University Sports Medical Centre in Groningen of the student athletes who wanted to participate in a college sports program were collected. The ECG characteristics were scored using computer-based measurements and the Seattle ECG criteria. Results: The study population included 1436 athletes, of which 72% were male. Male athletes were older (19.3 years vs. 18.6 years), participated in sports more frequently (4.0/week vs. 3.8/week) and spent more hours per week practising sports (6.4 h/week vs. 5.8 h/week) than female athletes. Male athletes had significantly higher PR intervals (149 ms vs. 141 ms), lead voltages and QRS duration (98 ms vs. 88 ms). Female athletes had significantly higher resting heart rates (69/min vs. 64/min) and QTc intervals (407 ms vs. 400 ms). Male athletes also had significantly higher amounts of sinus bradycardia (38.3% vs. 23.0%), incomplete RBBB (15.0% vs. 3.7%), early repolarisation (4.5% vs. 1.0%) and isolated QRS voltage criteria for LVH (26.3% vs. 4.6%). All P-values were =0.001. Conclusions: ECGs of young athletes demonstrate gender-related differences. These differences could be considered in their cardiovascular screening. For the Seattle ECG criteria we advise additional research into the clinical implications of using gender-based cut-off values for the QRS duration in the intraventricular conduction delay criterion. AUTORREFERAT